Pulsed Demand Modeling for the Optimal Placement of Water Quality Sensors in Water Distribution Networks. Issue 10 (29th September 2022) - Giudicianni, C.; Campisano, A.; Di Nardo, A.; Creaco, E.
Abstract: This paper deals with the issue of the consistency of water distribution network (WDN) modeling concerning the nature of demand for the optimal water quality sensor placement. In this regard, a biobjective optimization for the sensor placement is carried out by minimizing the contamination extension or the contaminated population in the trade‐off with the number of sensors installed, by considering two alternative demand modeling conditions, that is, smooth and pulsed demand, respectively. The real layout of the two Italian WDNs is considered for the application of the methodology. The results show that for a given placement of sensors, the contamination extension always increases when the pulsed demand is considered. Furthermore, optimal sensor positions are affected by the pulsed demand especially in the case of highly looped WDN layouts and when the extent of contamination is used as objective function. Key Points: Nodal demand modeling in water distribution networks influences the fate of contaminants moving through the system Layout and performance of a water quality sensor system differ if a stochastic bottom‐up approach is used for the demand modeling The extent of the influence of a different demand modeling depends on the monitoring target and on the water distribution network topology